Predictive value of Berlin Questionnaire and Epworth Sleepiness Scale for obstructive sleep apnea in a sleep clinic population. (16th January 2014) - Ulasli, Sevinc Sarinc; Gunay, Ersin; Koyuncu, Tulay; Akar, Olcay; Halici, Bilal; Ulu, Sena; Unlu, Mehmet
Abstract Introduction The Berlin Questionnaire (BQ) and Epworth Sleepiness Scale (ESS) are two of the widely used screening instruments for subjects suffering from sleep disorders. Objectives To determine the predictive accuracy of the BQ and ESS in the subjects who were admitted to our sleep clinic, using overnight polysomnography as the 'gold standard'. Methods The BQ and ESS were performed to 1450 subjects hospitalized in our sleep clinic for polysomnographic evaluation. Results One thousand two hundred thirty of 1450 subjects (84.8%) had apnea–hypopnea index (AHI) ≥ 5, and 70.5% of them were classified as being at high risk of sleep apnea with BQ and 45.9% of them were classified as having excessive daytime sleepiness with ESS. Being in the high‐risk group with the self‐reported, BQ predicted an AHI ≥ 5 with a sensitivity of 0.73 and a specificity of 0.44, vs a sensitivity of 0.46 and a specificity of 0.60 with the self‐reported ESS. Sensitivity of BQ (0.80) was highest when we selected the cut‐off value of AHI as 30. When we evaluated the predictive accuracy of BQ and ESS together, specificity of both instruments as 0.72 at AHI cut‐off value of 5 was found. AHIs were significantly correlated with the scores in each category and the total scores of BQ (P < 0.0001). Conclusions The BQ is a poor predictor of obstructive sleep apnea (OSA) in subjects admitted to our sleep clinic. BQ and ESS together may be used to detect patients with low risk for OSA.